2009
DOI: 10.1038/nbt.1580
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging distinguishes bona fide human iPS cells from partially reprogrammed cells

Abstract: Somatic cells can be reprogrammed into induced pluripotent stem (iPS) cells by enforced expression of transcription factors. Using serial live imaging of human fibroblasts undergoing reprogramming, we identified distinct colony types that morphologically resemble embryonic stem (ES) cells yet differ in molecular phenotype and differentiation potential. By analyzing expression of pluripotency markers, methylation at the OCT4 and NANOG promoters and differentiation into teratomas, we determined that only one col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
477
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(510 citation statements)
references
References 22 publications
26
477
4
1
Order By: Relevance
“…We replaced Tgfbr1 and Tgfb2 with Smad7, as Smad7 can block TGF-b signaling, which mimics the effects of downregulating Tgfbr1 and Tgfb2 [37,40]. An immunostaining assay for Rex-1, a specific pluripotency stem cell marker [41], was used to screen for iPS-like cells. We introduced all five genes (Smad7, Nanog, Nr6a1, Zfp371, and Zfp459) into the OKM cells by retroviral transduction (OKM-5F), which generated a much higher number of Rex-1-positive colonies compared with MEFs directly transduced with the four reprogramming factors (OSKM) or OKM cells transduced with Sox2 (OKM-S; Fig.…”
Section: One Critical Sox2 Signaling Pathway For Late-phase Ipsc Reprmentioning
confidence: 99%
“…We replaced Tgfbr1 and Tgfb2 with Smad7, as Smad7 can block TGF-b signaling, which mimics the effects of downregulating Tgfbr1 and Tgfb2 [37,40]. An immunostaining assay for Rex-1, a specific pluripotency stem cell marker [41], was used to screen for iPS-like cells. We introduced all five genes (Smad7, Nanog, Nr6a1, Zfp371, and Zfp459) into the OKM cells by retroviral transduction (OKM-5F), which generated a much higher number of Rex-1-positive colonies compared with MEFs directly transduced with the four reprogramming factors (OSKM) or OKM cells transduced with Sox2 (OKM-S; Fig.…”
Section: One Critical Sox2 Signaling Pathway For Late-phase Ipsc Reprmentioning
confidence: 99%
“…There are reports that suggest a fluctuating expression of Nanog in murine ESCs [34]. In contrast, other groups confirm bona fide human iPS cells by qRT-PCR for NANOG [18,25] and this correlation held true in downstream experiments such as teratoma formation in immunodeficient mice [18]. We also have chosen Nanog as a marker to identify truly reprogrammed murine iPS cells in situ.…”
Section: Live Screening Of Successfully Reprogrammed Murine Ttfs To Imentioning
confidence: 99%
“…However, in most cases, a definite verification of gene expression is impossible on living cells. The detection of endogenous pluripotency markers such as OCT4, SOX2, NANOG, GDF3, and REX1 requires fixation of the cells prior to staining [16][17][18] or is accomplished only after lysis by an RT-PCR analysis [17,18]. With such a manipulation, the cells are lost for further culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse intermediate reprogrammed cells can be labelled by stagespecific embryonic antigen (SSEA)-1 that is recognized as a specific marker of mouse embryonic stem cells (ESCs)/iPSCs [5][6][7] . We demonstrated that human cells positive ( þ ) for tumorrelated antigen (TRA)-1-60 8,9 induced by OSKM are intermediate reprogrammed cells to being iPSCs 10 . Behaviour of TRA-1-60 ( þ ) intermediate reprogrammed cells suggested that maturation, but not the initiation step, is a bottleneck of cell fate conversion towards human iPSCs.…”
mentioning
confidence: 99%